Chest pain, enzymes and hypothyroidism. Issue 893 (1st March 2000) - Strachan, S R; Afolabi, O; Brown, N; Gray, D
Abstract : Hypothyroidism is a common disorder and when presenting with classical symptoms and signs is easy to recognise. However, hypothyroidism may present in a manner suggestive of an acute myocardial infarction with an elevated creatine kinase and electrocardiographic abnormalities. We report a case of severe hypothyroidism presenting as a cardiac event whose symptoms and signs dispersed following treatment with thyroxine.